2011
DOI: 10.2527/jas.2010-3552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manipulation of the caspase system on myofibrillar protein degradation in vitro12

Abstract: Apoptosis via the intrinsic caspase 9 pathway can be induced by oxidative stressors hydrogen peroxide (H₂O₂) and N-(4 hydroxyphenol) rentinamide (fenretinide), a synthetic retinoid. Accelerated muscle atrophy and proteolysis in muscle-wasting conditions have been linked to oxidative stress and activated protease systems. Therefore, the hypothesis of this study was that proteolysis of myofibrillar proteins could be manipulated through the induction or inhibition of the caspase system. After slaughter, LM and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…[47] Previous researches have revealed that caspase-3 is capable of degrading a number of proteins in muscle. [9,48] In the current study, it is shown that the activities of cathepsin L and caspase-3 were increased by increasing heating time, and the higher level of activity could be sustained after 24 h (Fig. 2B,C), which may lead to the complete degradation of MHC and paramyosins, as shown in Fig.…”
Section: Discussionsupporting
confidence: 50%
“…[47] Previous researches have revealed that caspase-3 is capable of degrading a number of proteins in muscle. [9,48] In the current study, it is shown that the activities of cathepsin L and caspase-3 were increased by increasing heating time, and the higher level of activity could be sustained after 24 h (Fig. 2B,C), which may lead to the complete degradation of MHC and paramyosins, as shown in Fig.…”
Section: Discussionsupporting
confidence: 50%
“…All three apoptotic inducing treatments examined in this study resulted in a significant increase in caspase 3 activity, and the appearance of a 30 kDa proteolytic product assumed to originate from troponin T degradation and the generation of the caspase specific alpha II spectrin 120 kDa degradation product (SBDP120). Inhibition and activation of the caspase proteolytic system have also been demonstrated in myofibrils isolated from LD and supraspinatus muscles from normal and callipyge sheep (Kemp & Wheeler, 2011). Overall, results showed treatment with apoptotic inducers hydrogen peroxide and fenretinide reduced protein expression of the inactive latent isoform of caspase 9, indicating activation of the intrinsic apoptotic pathway.…”
Section: Caspase-mediated Post-mortem Proteolysismentioning
confidence: 77%
“…However, whilst treatment with apoptosis inducers fenretinide and hydrogen peroxide, and also recombinant caspase 3 can increase proteolysis in callipyge animals, which exhibit elevated levels of calpastatin, in comparison to control treatment, their effects were not substantial enough to overcome the limited proteolysis that these animals exhibit ( Fig. 3b; Kemp & Wheeler, 2011). The results from these studies accentuate the complexity of post-mortem proteolysis and meat tenderisation, and suggest that further research is required to understand the mechanisms behind it and the interactions between different proteolytic systems.…”
Section: Interactions Between the Caspase And Calpain Proteolytic Sysmentioning
confidence: 94%
See 1 more Smart Citation
“…Meat tenderness is directly correlated with the acceptability of meat by consumers and leads to consumers’ repurchase intent ( Kemp and Wheeler, 2011 ). Tenderness is determined by complex factors, including muscle water, the degradation of muscle skeleton proteins and protease enzymes that work postmortem ( He et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%